ENT 530 Business Model Canvas: Sweekiz Popcorn / Muhammad Haziq Ahmad Nazri ... [et al.] - Ahmad Nazri, Muhammad Haziq; Razali, Muhammad Izzam; Ghazali, Ahmad Adib; Mohd Shafuan, Nurul Faizah; Sabarudin, Nur Suriya; Mohd Fauzi, Siti Najiha; Abdul Latiff, Siti Syaradibah; Hassan A Gani, Samsiah (2021)
Sweekiz Popcorn is a business that offers products and services to the customer who likes to eat Popcorn that is delicious and sweet. It is suitable for all age groups. This business not only offers the products, but it is also a manufacturer of Popcorn to be used as goodies for weddings, parties, birthday parties and focuses on agents that want to sell Sweekiz Popcorn. Sweekiz Popcorn has established Bumiputera sole proprietorship to enterprise into the field of wedding goodies. The strategic location for this business operates in a developing housing area in Taman Lesung Batu Jaya, Alor Gajah, Melaka. Sweekiz Popcorn was established in 2012, and the business owners choose to venture into this field because they are confident in the experience, they have had for 6 years. Throughout this phase as well, the owners have started to be active in offering goodies for feasts and weddings around Melaka, Negeri Sembilan, Kuala Lumpur, and Johor Bahru. This Sweekiz Popcorn offers a variety of flavours which are caramel and chocolate in order to give a higher satisfaction level to the customer. The price of the Sweekiz Popcorn is also affordable for the customer based on the gram they want to buy which are 350g, 500g, and 170g. As an entrepreneur who has ventured into this field of business genuinely and yet on a small scale then the owner is targeting the desire in the near future to further expand this business on a larger scale. Sweekiz Popcorn will make every effort to achieve these goals. In a nutshell, this business uses Business Model Canvas (BMC) by listing out customer segments, value proposition, channels, key partners, key activities, customer relationship, key resources, cost structure, and revenue stream.